Guidance Of Qur'an Recitation Selection Activities At Tembilahan District Level - Munawaroh, Faridatul; Nur , Syamsiah; Khasanah , Ulfaniatul; Sariyani, Sariyani (CV. Pustaka An Nur, 2025)
Reading and applying the contents of the verses of the Qur'an is a noble deed, especially if someone wants to memorize the Qur'an, understand and practice the Qur'an in all aspects of daily life. In this Qur'an recitation selection, there is indeed an arena for competing skills, but there are also other things to spread da'wah. Which is useful for motivating and creating a strong desire to follow the activity. This service is carried out for the Qur'an recitation selection at the Tembilahan sub-district level, Indragiri Hilir Regency. The service method uses the Participatory Action Learning System (PALS) method, which is a method that emphasizes the activeness and participation of partners in the Qur'an recitation selection activities in the form of a panel of judges, MC, and mentors for each competition. The results of the service show that there is motivation and practice of coordinating with fellow partners. This can be seen from the increase in mastery of the ability to read the Qur'an.Thus, we want to play an active role in supporting them to remain enthusiastic in broadcasting the Qur'an and studying it by holding a selection of Qur'an recitation assistance which is expected to spur their motivation in studying and memorizing the Qur'an.